Analisis Administrasi Pendidikan Tentang Konsep Manajemen dalam Pandangan Al-Qur’an - Ovi Soviya; Sibawaihi Sibawaihi; Sulaeman Sulaeman (Madania: Jurnal Ilmu-Ilmu Keislaman, 2023)
The purpose of this research is to analyze the concept of management of Islamic education in the view of the Qur'an, including flexible, effective, efficient, open, cooperative and participatory and also to analyze the components of management of Islamic education contained in the Al-Qur'an which consists of of planning, organizing, actuating, and evaluating. The method used in this research is a qualitative method with a library research approach, the subjects in this study are journals, scientific articles, books and those related to this research. The data analysis technique used in this research is to categorize, manage, and isolate redundant data in a way that leads to definite and testable conclusions. Classify journals and articles related to educational administration analysis of management concepts in the view of the Koran. The results of this study are that education management in the view of the Koran is an activity to mobilize and integrate all educational resources to achieve the goals of Islamic education that have been set. To understand the management of Islamic education, there are several factors that must be considered by all administrators, namely: planning, organizing, actuating, and controlling.